2019
DOI: 10.1073/pnas.1815361116
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-sensitive upstream ORF controls PRL phosphatase expression to mediate energy metabolism

Abstract: Phosphatases of regenerating liver (PRL-1, PRL-2, and PRL-3, also known as PTP4A1, PTP4A2, and PTP4A3) control magnesium homeostasis through an association with the CNNM magnesium transport regulators. Although high PRL levels have been linked to cancer progression, regulation of their expression is poorly understood. Here we show that modulating intracellular magnesium levels correlates with a rapid change of PRL expression by a mechanism involving its 5′UTR mRNA region. Mutations or CRISPR-Cas9 targeting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 61 publications
6
64
0
Order By: Relevance
“…For example, decreased intracellular Mg 2+ levels suppress cell cycle progression and are consequently associated with cell growth impairment [2]. Recent studies therefore have focused on intracellular Mg 2+ concentration as a central mechanism for cellular metabolism and proliferation [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, decreased intracellular Mg 2+ levels suppress cell cycle progression and are consequently associated with cell growth impairment [2]. Recent studies therefore have focused on intracellular Mg 2+ concentration as a central mechanism for cellular metabolism and proliferation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular Mg 2+ and ATP levels are closely associated, as ATP must be bound to this cation to be biologically active[1]. Indeed, previous studies have shown that PRL-2 knockdown and decreased intracellular Mg 2+ levels, reduce intracellular ATP levels and regulate cellular metabolism[3][57].Given that ARL15 overexpression reduced CNNM-mediated Mg 2+ uptake, the expression of ARL15 may indirectly regulate cellular metabolism. Indeed, ARL15 has been associated with a wide range of metabolic parameters and diseases in GWAS, including adiponectin, HDL, diabetes mellitus and body shape[58][59][60][61][62][63].As these studies did not analyze Mg 2+ status as a modifying factor, it cannot be excluded that ARL15 has additional functions that explain these associations.…”
mentioning
confidence: 99%
“…26,27 A recent study reported the dysregulation of uORF in tumors and its important regulatory role in tumorigenesis. 28 In this study, TFAP4-66aa-uORF was downregulated in glioma tissues and in glioma cells. Overexpression of TFAP4-66aa-uORF inhibited the malignant biological behavior of glioma cells.…”
Section: Discussionmentioning
confidence: 53%
“…Its primary function is to regulate the translation of the mRNA CDS region . A recent study reported the dysregulation of uORF in tumors and its important regulatory role in tumorigenesis . In this study, TFAP4‐66aa‐uORF was downregulated in glioma tissues and in glioma cells.…”
Section: Discussionmentioning
confidence: 56%
“…CPuORF 38 , as a positive control. Besides the PTP4A1 CPuORF, we selected CPuORFs with well-conserved C-terminal regions.…”
Section: Sequence-dependent Effects Of Cpuorfs On Morf Translationmentioning
confidence: 99%